Elaboração de Animações Gráficas para Atividade de Aprendizagem da dilatação Térmica Linear no Ensino Médio - Calegari, Renato (2010)
The work presented here describes the construction of an educational hypermedia application for the content of Linear Thermal Expansion in teaching physics in high school. The hypermedia application was created in flash that allows light to be run on any machine and have a look capable of holding the attention of the student. Through the use of hypermedia application the teacher can make a coaching activity that the student is developing through the feedback procedure. Thus, allows the teacher to remotely monitor the activity done by the students, analyzing the construction of their knowledge and can intervene when necessary, allowing learning to be more significant. Is the Theory of Meaningful Learning of Ausubel which is the foundation of this work. This work is also given a questionnaire that can be applied to students before using the hypermedia application, in order to obtain student information through the use of new technologies in the classroom and in their daily lives. This application is directed to education, since it addresses only the construction of a hypermedia application and not its application. Through the feedback procedure the teacher follows the construction of knowledge that the student will have by using this feature, showing that a material which, when used by the student will be able to bring significant contributions to physics teaching in the content of linear thermal expansion in high school .